The Wager : a tale of shipwreck, mutiny and murder - Grann, David (New York: Doubleday, 2023)
This tale of shipwreck, survival and savagery...recounts the events on His Majesty$1 (Bs Ship The Wager, a British vessel that left England in 1740 on a secret mission, resulting in a court martial that revealed a shocking truth.s
Prologue -- Part one: The wooden world. The first lieutenant ; A gentleman volunteer ; The gunner -- Part two: Into the storm. Dead reckoning ; The storm within the storm ; Alone ; The gulf of pain -- Part three: Castaways. Wreckage ; The beast ; Our new town ; Nomads of the sea ; The Lord of Mount Misery ; Extremities ; Affections of the people ; The ark ; My mutineers -- Part four: Deliverance. Byron's choice ; Port of God's Mercy ; The haunting ; The day of our deliverance -- Part five: Judgment. A literary rebellion ; The prize ; Grub Street hacks ; The docket ; The court-martial ; The version that won -- Epilogue.
Maps on lining papers.
Includes bibliographical references (pages 265-313) and index.
Keywords: Shipwrecks; Shipwreck victims; Mutiny -- Great Britain; Shipwreck victims -- Great Britain; Shipwreck victims -- Patagonia (Argentina and Chile); Wager (Ship)